LPS stimulates gingival fibroblasts to express PD-L1 via the p38 pathway under periodontal inflammatory conditions. (September 2021) - Zhou, Kecong; Sun, Mengjun; Xia, Yiru; Xie, Yufeng; Shu, Rong
Highlights: PD-L1 expression in HGFs of periodontitis patients is higher than healthy controls. PD-L1 is up-regulated in HGFs of inflammatory group after LPS stimulation. The p38 pathway is involved in PD-L1 expression in inflammatory HGFs. Abstract: Objective: The overall aim of this research was to investigate the differences in the expression of programmed death ligand 1 (PD-L1) in human gingival fibroblasts (HGFs) between a periodontal healthy group and a periodontal inflammatory group. and explore the possible mechanism involved. Methods: Differences in PD-L1 mRNA and protein expression in HGFs from a periodontal healthy group and a periodontal inflammatory group were examined by qPCR and western blotting, respectively, and were further tested after lipopolysaccharide (LPS) stimulation in both groups. The effects of a p38 pathway inhibitor on the changes in p38 phosphorylation levels and PD-L1 expression after LPS stimulation were investigated in both groups. Results: PD-L1 mRNA and protein levels in HGFs in the periodontal inflammatory group were significantly higher than those in the periodontal healthy group ( p < 0.05). After 10 μg/mL LPS stimulation, PD-L1 mRNA levels in HGFs from both groups increased significantly ( p < 0.05), peaking at 4 h, and the peak was significantly higher in the periodontal inflammatory group than in the periodontal healthy group ( p < 0.05). However, PD-L1 protein expression was upregulated only in the inflammatory group ( p < 0.05). Inhibition of the p38 pathway in HGFs decreased p38 phosphorylation in both groups ( p < 0.05) but this treatment reversed the LPS-induced increase in PD-L1 mRNA and protein levels only in the inflammatory group ( p < 0.05). Conclusion: In the periodontal inflammatory state, the expression of PD-L1 in HGFs is more easily activated, and may be influenced by the p38 pathway.